2014
DOI: 10.1039/c4ob01658k
|View full text |Cite
|
Sign up to set email alerts
|

Design and synthesis of a new dimeric xanthone derivative: enhancement of G-quadruplex selectivity and telomere damage

Abstract: Following the results we previously reported on a series of xanthene and xanthone derivatives as G-quadruplex stabilizing ligands, in order to obtain a more selective compound with respect to the previous generation of derivatives, we decided to modify the structure of the core ligand, specifically its aromatic extension. In particular, here we report the design, synthesis and activity data of a new compound obtained by dimerization of the xanthene core (HELIXA4C). The reported results show that extension of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…Upon irradiation with ultraviolet light, which induces the photoconversion 38.6 into 38.7 , these nanotubes are disassembled at a rate that is dependent on the irradiation wavelength and light intensity. A substituted helixanthene derivative, 38.11 , synthesized in 2014 by Franceschin, Altieri, et al, revealed its potential for stabilizing telomeric G-quadruplex DNA . The improved selectivity of 38.11 was demonstrated using ESI–MS data, in vitro cancer screening, and specific immunofluorescence assays.…”
Section: Perylenoidsmentioning
confidence: 99%
See 1 more Smart Citation
“…Upon irradiation with ultraviolet light, which induces the photoconversion 38.6 into 38.7 , these nanotubes are disassembled at a rate that is dependent on the irradiation wavelength and light intensity. A substituted helixanthene derivative, 38.11 , synthesized in 2014 by Franceschin, Altieri, et al, revealed its potential for stabilizing telomeric G-quadruplex DNA . The improved selectivity of 38.11 was demonstrated using ESI–MS data, in vitro cancer screening, and specific immunofluorescence assays.…”
Section: Perylenoidsmentioning
confidence: 99%
“…A substituted helixanthene derivative, 38.11, synthesized in 2014 by Franceschin, Altieri, et al, revealed its potential for stabilizing telomeric G-quadruplex DNA. 197 The improved selectivity of 38.11 was demonstrated using ESI−MS data, in vitro cancer screening, and specific immunofluorescence assays.…”
Section: Chemical Reviewsmentioning
confidence: 99%
“…7 Since then, the biological application of G-quadruplexes has received a lot of attention in the search for novel cancer therapeutics 8 and in the eld of structure-based drug design. 9 These studies have shown that planar aromatic ligands, molecules based on macrocyclic or helically folded oligomers, porphyrin-like units 10,11 and some natural products like telomestatin displayed a clear preference for recognizing, binding and stabilizing G-quadruplexes. [12][13][14][15] Besides their importance in gene expression regulation, 16 some G-quadruplexes have been also described as potential anti-HIV drugs due to their capacity to interact with proteins present in HIV-1 infections.…”
Section: Introductionmentioning
confidence: 99%
“…89,[206][207][208][209][210][211][212][213][214][215][216][217][218] 7 Diversification on the xanthone core Hydroxyl groups are undoubtedly one of the most versatile functional groups when it comes to structural modifications (Scheme 26). A myriad of examples have been described in the literature, including the reaction with alkyl halides for the transformation into alkoxy, 43,59,69,[219][220][221][222][223] haloalkoxy, 18,51,69,99,224 methyl alkyl-or aryl-piperazine moieties, 225 epoxypropanoxy 65,103,[220][221][222] oxirane 221 , oxypropanolamines, 103 benzenesulfonamides, 226 and propargyloxy. 45,52,54,63,106,118,173,227,228 When reacted with other compounds that are not alkyl halides, several other functional-Scheme 25 Other methodologies for the synthesis of xanthones.…”
Section: Synthesis Of Azaxanthone-derivatives: the Case Of Fivemembermentioning
confidence: 99%